Principles For Sustainable Riverfront Development For Malaysia - Md. Yassin, Azlina; Bond, Sandy; McDonagh, John (Journal of Techno-Social, 2012)
River and water are important resources for human life, environment and national development. In Malaysia, the importance of rivers as the focal point of the city was established from early times of civilisation and remains forever. Population and economic growth, urbanisation and increased technology have transformed many Malaysian river systems from water industries into non water industries. Due to these changes, the function of the riverfront areas have also changed and the current pattern of riverfront development in Malaysia now focus more on mixed-use development and recreation. Presently, numbers of riverfront development projects were developed in Malaysia for recreation, residential, and mixed-use. Unfortunately, in most cases, the developments identified are not successful whereby, having cost effects more than economic value. For example, increases in water pollution indexes and rates of juvenile problems. The focus of this study was to examine waterfront development in Malaysia as well as to identify the attributes of waterfront development, in order to develop guidelines for waterfront development. The findings of this research were based on interviews conducted with Government officers, Property developers, and the Waterfront community from three case study areas (qualitative phase), and from questionnaires mailed and e-mailed to property development companies listed under Bursa Malaysia (quantitative phase). The findings identified 18 attributes to be used in assisting developers when undertaking waterfront projects in the future. The attributes identified were then recommended to be used as guidelines of best practices of riverfront development in Malaysia.